A Multi-Scale DNN Algorithm for Nonlinear Elliptic Equations with Multiple Scales (Communications in Computational Physics, 2020)
Algorithms based on deep neural networks (DNNs) have attracted increasing attention from the scientific computing community. DNN based algorithms areeasy to implement, natural for nonlinear problems, and have shown great potential toovercome the curse of dimensionality. In this work, we utilize the multi-scale DNN-based algorithm (MscaleDNN) proposed by Liu, Cai and Xu (2020) to solve multi-scaleelliptic problems with possible nonlinearity, for example, the p-Laplacian problem.We improve the MscaleDNN algorithm by a smooth and localized activation function.Several numerical examples of multi-scale elliptic problems with separable or non-separable scales in low-dimensional and high-dimensional Euclidean spaces are usedto demonstrate the effectiveness and accuracy of the MscaleDNN numerical scheme.
Keywords: Multi-scale elliptic problem; p-Laplacian equation; deep neural network (DNN); variational formulation; activation function.